Intersex human rights, sexual orientation, gender identity and the Yogyakarta Principles. (20th October 2021) - Carpenter, M
Abstract: Background: Intersex people are at risk of human rights abuses because their bodies do not fit medical and social norms for female or male bodies. The 2006 Yogyakarta Principles aim to promote good practices in protecting the rights of LGBT and intersex people by applying human rights law in relation to 'sexual orientation' and 'gender identity'. They were ineffective in protecting the rights of intersex people, including due to an inappropriate framing around sexual orientation and gender identity. In the same year, a group of clinicians published a 'consensus statement' reframing intersex traits as 'disorders of sex development', reinscribing medical authority over intersex bodies. In 2015 a first country (Malta) enacted protections of rights to bodily integrity and physical autonomy and freedom from discrimination, associated with a new attribute of 'sex characteristics'. Methods: In January 2017, the International Service for Human Rights and ARC International issued a call for submissions to supplement the Yogyakarta Principles, and brought together a drafting team. The Asia Pacific Forum of National Human Rights Institutions and United Nations Development Program also held a gender- and geopolitically-balanced conference to mark a decade of the original Principles and produce recommendations. An expert meeting was held in Geneva in September 2017 to agree the update. Results: The 'Yogyakarta Principles plus 10' elaborated a new attribute of sex characteristics and recognised rights to bodily integrity, truth and legal recognition. These directly respond to the human rights situation of intersex people, with relevance to intersex populations, healthcare workers, advocates, and policymakers. Conclusions: Adoption of the new attribute and attention to the new Principles can help address the human rights of people with intersex variations within health, education, and other social policy settings.